Fueling Culture - Wenzel, Jennifer,Yaeger, Patricia,Szeman, Imre (Fordham University Press, 2017)
How has our relation to energy changed over time? What differences do particular energy sources make to human values, politics, and imagination? How have transitions from one energy source to another—from wood to coal, or from oil to solar to whatever comes next—transformed culture and society? What are the implications of uneven access to energy in the past, present, and future? Which concepts and theories clarify our relation to energy, and which just get in the way? Fueling Culture offers a compendium of keywords written by scholars and practitioners from around the world and across the humanities and social sciences.- These keywords offer new ways of thinking about energy as both the source and the limit of how we inhabit culture, with the aim of opening up new ways of understanding the seemingly irresolvable contradictions of dependence upon unsustainable energy forms.Fueling Culture brings together writing that is risk-taking and interdisciplinary, drawing on insights from literary and cultural studies, environmental history and ecocriticism, political economy and political ecology, postcolonial and globalization studies, and materialisms old and new.Keywords in this volume include: Aboriginal, Accumulation, Addiction, Affect, America, Animal, Anthropocene, Architecture, Arctic, Automobile, Boom, Canada, Catastrophe, Change, Charcoal, China, Coal, Community, Corporation, Crisis, Dams, Demand, Detritus, Disaster, Ecology, Electricity, Embodiment, Ethics, Evolution, Exhaust, Fallout, Fiction, Fracking, Future, Gender, Green, Grids, Guilt, Identity, Image, Infrastructure, Innervation, Kerosene,- Lebenskraft, Limits, Media, Metabolism, Middle East, Nature, Necessity, Networks, Nigeria, Nuclear, Petroviolence, Photography, Pipelines, Plastics, Renewable, Resilience, Risk, Roads, Rubber, Rural, Russia, Servers, Shame, Solar, Spill, Spiritual, Statistics, Surveillance, Sustainability, Tallow, Texas, Textiles, Utopia, Venezuela, Whaling, Wood, Work For a full list of keywords in and contributors to this volume, please go to: http://ow.ly/4mZZxV
10.1515/9780823273935
Keywords: anthropocene; climate change; cultural studies; culture and society; ecocriticism; energy; environmental studies; global warming; natural resources; oil; SCIENCE / Life Sciences / Ecology